Pathologies of Studying Public Opinion, Political Communication, and Democratic Responsiveness - Druckman, James N. (Political communication, 2014)
Research on democratic representation and public opinion formation has largely ignored one another. Once one considers the reality of the political communication environment, a fundamental tension between these two literatures emerges. In this essay, I review work on each, highlighting problems with both how "quality opinion" is often defined and how representation is typically studied. I then offer a way forward.